41‐1: Strong Effect of Azodye Layer Thickness on RM‐Stabilized Photoalignment. Issue 1 (2nd June 2017) - McGinty, Colin; Finnemeyer, Valerie; Reich, Robert; Clark, Harry; Berry, Shaun; Bos, Philip
Abstract : We have previously proposed a process for stabilizing azodye photo‐alignment layers using a surface localized reactive mesogen (RM) layer applied by dissolving the monomer in a liquid crystal prior to filling the cell. Surprisingly, thin azodye layers (~3 nm) exhibit improved stability upon exposure to polarized light compared to thicker layers (~40 nm).